Comparison of bipolar sub-modules for the alternate arm converter - Wickramasinghe, Harith R. (2017)
The alternate arm converter (AAC) is an emerging dc-fault tolerant multilevel converter topology aimed at high-power and HVDC applications. This paper addresses the suitability of modular multilevel converter (MMC) submodules (SMs) for the AAC. Bipolar SMs are applicable for AACs depending on the complexity, controllability, device count, and operating losses. However, only the full-bridge SM (FB-SM) and the cross-connected SM (CC-SM) are fully controllable and functional in AACs. Based on the loss analysis of FB-SM- and CC-SM-based AAC with different device configurations, it is shown that: (i) complex SM structures do not benefit the operation of AAC, and (ii) the FB-SM provides the most functional advantages in an AAC.